Assessment of Physical, Chemical, and Heavy Metal Parameters of Drinking Water in Specific Locations in The Ciledug Area, Tangerang City - Meyliana Wulandari; Eka Noviana Safitri; Sasya Adhalya Fajra; Zahratussaadah Zahratussaadah; Widiastuti Agustina Eko Setyowati; Herlinawati Herlinawati (Jurnal Ilmu Lingkungan, 2026)
Drinking water is an essential necessity for human life; however, its quality is often threatened by increasing industrial activities, urbanization, and environmental pollution. To support the achievement of Sustainable Development Goal (SDG) 6, which aims to ensure the availability and sustainable management of clean water, an evaluation of drinking water quality was conducted in some areas in Ciledug area, Tangerang City. This study aimed to assess the compliance of drinking water quality with the applicable drinking water quality standards based on physical, chemical, and heavy metal parameters. The study involved the measurement of pH, temperature, turbidity, dissolved oxygen (DO), total dissolved solids (TDS), electrical conductivity (EC), and salinity, followed by laboratory analyses of ammonia using the phenate method, phosphate using the ascorbic acid method, and Fe and Mn using Atomic Absorption Spectrometry (AAS). The results showed that six drinking water samples complied with the drinking water quality standards stipulated in the Indonesian Minister of Health Regulation No. 2 of 2023, whereas two samples (F and H) failed to comply due to high turbidity (17.9 NTU) and low pH (5.6). Ammonia concentrations were below the permissible limit of 0.5 mg/L, while one sample exceeded the limit with a concentration of 1.690 mg/L. Phosphate concentrations in all samples were below the permissible limit of 0.2 mg/L, whereas Fe and Mn were not detected. Overall, most drinking water samples complied with the quality standards. Continuous monitoring of parameters that deviate from the quality standards is necessary to ensure the provision of safe drinking water and to support the implementation of SDG 6 at the local level.